Pengaruh Corporate Governance dan Intellectual Capital Terhadap Nilai Perusahaan - Fitriyani Fitriyani; Fitra Dharma; Retno Yuni Nur Susilowati (Goodwood Publishing, 2022)
Mechanism of corporate governance, independent commissioners and institutional ownership with intellectual capital as independent variables in this study examines positive influence on firm value. Using a research sample of cyclical sector companies on the IDX in 2017-2020 with a total of 352 data observations. The test instrument is multiple linear regression analysis processed using the SPSS 26 application. The results found that independent commissioners have a negative effect on firm value, institutional ownership has an effect on firm value and intellectual capital has a negative effect on firm value in cyclical sector companies on the IDX in 2017- 2020.